CFD predictions of drilling fluid velocity and pressure profiles in laminar helical flow - Pereira,F. A. R. (2007)
Fluid flow in annular spaces has received a lot of attention from oil industries, both in drilling operations and in petroleum artificial rising. In this work, through numerical simulation using the computational fluid dynamics (CFD) technique, the flow of non-Newtonian fluids through the annuli formed by two tubes in concentric and eccentric arrangements of a horizontal system has been investigated. The study analyzes the effects of viscosity, eccentricity, flow and shaft rotation on the tangential and axial velocity profiles and on the hydrodynamic losses. It evaluates the performance of the numerical method used, comparing the results obtained with those in other reported works, aiming to validate the simulation strategy by the interpolation routines as well as the couplings algorithms adopted.